2017
DOI: 10.1200/jco.2016.69.3564
|View full text |Cite
|
Sign up to set email alerts
|

Response to Rituximab Induction Is a Predictive Marker in B-Cell Post-Transplant Lymphoproliferative Disorder and Allows Successful Stratification Into Rituximab or R-CHOP Consolidation in an International, Prospective, Multicenter Phase II Trial

Abstract: The Sequential Treatment of CD20-Positive Posttransplant Lymphoproliferative Disorder (PTLD-1) trial (ClinicalTrials.gov identifier, NCT01458548) established sequential treatment with four cycles of rituximab followed by four cycles of cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) chemotherapy as a standard in the management of post-transplant lymphoproliferative disorder (PTLD) and identified response to rituximab induction as a prognostic factor for overall survival. We hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
172
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(192 citation statements)
references
References 27 publications
5
172
1
1
Order By: Relevance
“…The minority of patients who were judged fit enough to receive subsequent chemotherapy still only had a median OS of 1·5 years and a two‐year OS of 45%. In this respect, our outcomes were inferior to those observed in clinical trials, where 90% of patients who did not achieve CR went on to chemotherapy and attained a median OS of >2 years (Trappe et al , ; Trappe et al , ). Patients may be more difficult to salvage in the real‐world setting.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The minority of patients who were judged fit enough to receive subsequent chemotherapy still only had a median OS of 1·5 years and a two‐year OS of 45%. In this respect, our outcomes were inferior to those observed in clinical trials, where 90% of patients who did not achieve CR went on to chemotherapy and attained a median OS of >2 years (Trappe et al , ; Trappe et al , ). Patients may be more difficult to salvage in the real‐world setting.…”
Section: Discussioncontrasting
confidence: 79%
“…Ultimately, patients who attained CR after R‐induction were safely treated with R‐alone, and patients with PR, SD or PD were effectively managed by the addition of R‐CHOP. At a median follow‐up of 4·5 years, 82% of patients continued in remission at three years with a median OS of 6·6 years (Trappe et al , ). Notably, TRM was 8% in the trial using this strategy.…”
mentioning
confidence: 99%
“…With regard to B cells, it has previously been reported that cyclosporine and tacrolimus increase the viability of spontaneous EBV-lymphoblastoid cell lines, possibly reflecting partial protection from Fas-mediated apoptosis, and this phenomenon may also occur in vivo and play a role in the pathogenesis of posttransplant lymphoproliferative disorder (22). Conversely, antibody-mediated B cell depletion has long been recognized as an effective intervention for EBV-associated posttransplant lymphoproliferative disease (4,23). The EBV latency reservoir is the resting B cell reservoir, and depleting the B cell reservoir reduces both the pool of infected cells and those that might become infected (24).…”
Section: Discussionmentioning
confidence: 99%
“…98,99 Standard full-dose CHOP (Cyclophosphamide; Hydroxydaunorubicin or doxorubicin; Oncovin or vincristine; Prednisone) regimen chemotherapy in PTLD has been associated with substantial adverse events and higher treatment-related mortality. 101 In children, a prospective multicenter trial of reduced intensity CHOP chemotherapy showed a 2-year overall survival rate of 73% and reduced the treatment related mortality, but did not work well in fulminant PTLD. In the multicenter prospective European PTLD-1 trial, early rituximab, followed by full dose CHOP chemotherapy if insufficient response to rituximab alone, resulted in 68% complete response, an additional 22% partial response, a median overall survival of 6.6 years, and treatment-related mortality of only 11%.…”
Section: Treatment Of Ptlds/nhlsmentioning
confidence: 99%
“…In a subsequent trial, treatment stratification into rituximab or rituximab plus CHOP consolidation, on the basis of response to rituximab induction, was both safe and effective, with complete response rate of 70% and median overall survival of 6.6 years. 101 In children, a prospective multicenter trial of reduced intensity CHOP chemotherapy showed a 2-year overall survival rate of 73% and reduced the treatment related mortality, but did not work well in fulminant PTLD. 102 Addition of rituximab to reduced intensity CHOP chemotherapy resulted in responses even in fulminant PTLD, with 2-year overall survival of 83%.…”
Section: Treatment Of Ptlds/nhlsmentioning
confidence: 99%